Analisis Pengurangan Cooling Water Loss Menggunakan Six Sigma dan Failure Mode Effect Analysis (FMEA) - Ikhsan Wicaksono; Tri Joko Wibowo; M. Jihan Shofa (Universitas Serang Raya, 2017)
Loss on a working system is one of the causes of the cost of the process to swell. The loss that reaches more than 450 tons/month on a cooling water system at a chemical company in the Serang area causes the company's expenses to swell. This study aims to determine the cause of cooling water wash as a basis for process improvement by using Six Sigma and Failure Mode Effect Analysis (FMEA). Data analysis results showed that cooling water loss is too little backwash filter duration, service filter duration is not optimum, and flow unreadable side stream. Improvements by increasing the length of the backwash, raising the service time of the sand filter to every two days, and cleaning the rotameter can increase the sigma value from 3.5 to 4.5.